A parametric evaluation of powder flowability using a Freeman rheometer through statistical and sensitivity analysis: A discrete element method (DEM) study. (2nd February 2017) - Wilkinson, S.K.; Turnbull, S.A.; Yan, Z.; Stitt, E.H.; Marigo, M.
Graphical abstract: Highlights: Simulation outcomes using DEM are strongly influenced by 'chosen' input parameters. Case study of simulation of a Freeman Rheometer to characterise powder flowability. Design of simulations used to extensively explore impact of parameter inputs. Results analysed via effects/interactions model and principal component analysis. Methodology provides parameter calibration roadmap for Freeman Rheometer. Abstract: The flowability of powders in a Freeman Rheometer (FT4) is explored in this study using discrete element method (DEM). Five DEM input parameters describing particle properties: static and rolling friction coefficients, coefficient of restitution, Young's modulus and cohesion energy density (using JKR cohesion model) were explored in a matrix of simulations using Design of Simulation (DoS) principles. The impact of these parameters was assessed against two responses from the FT4 test: the basic flowability energy (BFE) and specific energy (SE). By using a combination of empirical effects and interactions analysis and principal component analysis (PCA), it was found that static and rolling friction parameters play a critical role in determining the BFE and SE of a powder, whilst cohesion energy density also plays a significant role in influencing BFE. The combination of these methods has helped deliver a roadmap to show which parameters would be effectively calibrated on an FT4.